2004
DOI: 10.1109/tnb.2004.837903
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Rare Cell Fractionation Device: Application for Cancer Detection

Abstract: Isolating rare cells from biological fluids including whole blood or bone marrow is an interesting biological problem. Characterization of a few metastatic cells from cancer patients for further study is desirable for prognosis/diagnosis. Traditional methods have not proven adequate, due to the compositional complexity of blood, with its large numbers of cell types. To separate individual cells based on their mechanical characteristics, we have developed a series of massively parallel microfabricated sieving d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(64 citation statements)
references
References 28 publications
0
64
0
Order By: Relevance
“…The past decade has seen many new technologies proposed for biological cell sorting and analysis on microchips. Arrays with pillars of varying geometries have been used to fractionate cells in blood and capture tumor cells (37 ). Similarly, crescent-shaped trap arrays with a fixed 5-m gap width within microfluidic chambers have been used to enrich CTCs from whole blood without preprocessing (38 ).…”
Section: Methods Based On Physical Propertiesmentioning
confidence: 99%
“…The past decade has seen many new technologies proposed for biological cell sorting and analysis on microchips. Arrays with pillars of varying geometries have been used to fractionate cells in blood and capture tumor cells (37 ). Similarly, crescent-shaped trap arrays with a fixed 5-m gap width within microfluidic chambers have been used to enrich CTCs from whole blood without preprocessing (38 ).…”
Section: Methods Based On Physical Propertiesmentioning
confidence: 99%
“…The desire to generate isolation systems that are more readily amenable to diagnostic use has led to a growth in the design of microfluidic, lab-on-a-chip type systems capable of separating and capturing particles of different sizes. Many techniques have been developed using microfluidics to separate microparticles, using methods such as a combination of centrifugal force and graduated mechanical gap (Maruyama et al 2010), flow splitting and recombining (so-called biomimetic devices that rely on size-based variations in particle behavior when in laminar flow) (Takagi et al 2005;Yamada and Seki 2006;Andersen et al 2009); optical fractionation (MacDonald et al 2003;Ladavac et al 2004;Milne et al 2007;Smith et al 2007), or deterministic lateral displacement arrays, which function much like a particle sieve (Huang et al 2004;Mohamed et al 2004;Loutherback et al 2010). Research has also demonstrated that it is possible to isolate shed microvesicles from the cells of origin based on size discrimination using dielectrophoretic sorting.…”
Section: Isolation and Separation Formats For Shed Vesicle Populationsmentioning
confidence: 99%
“…However, they typically require additional labels. Size, without labels, has also been used to isolate rare blood components by using filter-based methods (6). The removed component may be harvested by periodically stopping the flow into the filter and flushing to remove the desired particles from the filter mesh.…”
mentioning
confidence: 99%